Implementation of multi-hop lora network for centralized remote display of running text message based on IoT - Morlan Pardede; Elferida Hutajulu; Regina Sirait; Junaidi Junaidi; Arnold Pakpahan (Jurnal Mantik, 2023)
Running text is a promotional and information billboard made by LED. It can be programmed by using a computer to display text, images, and animations. Running text makes people interested to read some message because a color of the lights and animation. For wide location such as campuses, airports and many more place, several running texts are needed. It’s difficult to change some message manually one by one. It will spend energy and time. To solve the problem, this research was conducted to create a system to display of messages on three running texts centrally using a multihop LoRa wireless network. Each running text board consists of four P10 panel boards, an ESP 32 as a microcontroller, and a LoRa SX1276 as a sender and receiver. Message setting is done from a computer connected to the Gateway or from an android phone via Telegram bot. The results are LoRa power 10 dBm, distance between nodes can be reached 110 m. The amount of round-trip time (RTT) for point to point is 103 ms and for two hops of 1221 ms. The length of the message that can be sent 256 characters with the character patterns available in the DMD 32 library. This system is very suitable to support areas where internet is not available. The signal emitted by LoRa is Line of sight for achieve maximum coverage. The antenna between the nodes must be installed facing without obstruction